Pengaruh Dispersi Padat Irbesartan-Poloxamer 188 Terhadap Tekanan Darah dan Kadar Nitric Oxide (NO) Pada Tikus Putih Jantan Hipertensi - Fifi Harmely; Ellyza Nasrul; Salman Umar; Erizal Zaini; Yufri Aldi (Jurnal Sains Farmasi & Klinis, 2018)
A research on formulation of edible film from basil leaves extract as mouth freshener has been done. The extract of basil leaves were used in various concentrations which are 2.5%, 5% and 7.5%. The products were evaluated for some parameters such as organoleptic, friability, drying shrinkage, pH, thickness, flavonoid contents and respondents preference. The results of evaluation showed that edible filmsfrom basil leaves extract meet requirements as required by Standard Nasional Indonesia (SNI) and have such quality as product in the market. Statistical analysis using Kruskal Wallis test showed that respondents preferred for the F0 formulation in term of their appearance and taste while as mouth freshener, respondents preferred the F3 formulation.